Compressive behavior for recycled aggregate concrete confined with recycled polyethylene naphthalate/terephthalate composites. (20th November 2020) - Han, Qiang; Yuan, Wan-Ying; Ozbakkaloglu, Togay; Bai, Yu-Lei; Du, Xiu-Li
Highlights: The first experimental study of large rupture strain (LRS) FRP-confined recycled aggregate concrete (RAC) was conducted. The effect of replacement ratio of recycled aggregate and confinement stiffness was investigated. The stress–strain behavior and the ultimate condition were discussed. The applicability of the existing stress–strain models to LRS FRP-confined RAC was evaluated. Abstract: Environmentally friendly recycled aggregate concrete (RAC) is a good alternative to natural aggregate concrete (NAC). The poor performance of RAC (e.g., relatively lower strength than its NAC counterpart) that limits its engineering application can be improved by the lateral confinement of fiber-reinforced polymer (FRP). A new type of FRP emerged in recent years and made from recycled polyethylene naphthalate (PEN)/terephthalate (PET) fibers has a large rupture strain (LRS, typically greater than 5%). It is ideal for confining RAC, especially to satisfy the ductility requirements of structures in earthquake zones. In this study, 40 RAC circular specimens wrapped with LRS FRP were tested for monotonic compressive behavior. The replacement ratio of recycled coarse aggregate and the confinement stiffness of FRP were experimentally studied. Test results indicate that the enhancement of compressive strength and strain of RAC is mainly affected by the confinement stiffness, but marginally affected by the replacement ratio. Furthermore, the results show that the design-oriented model and analysis-oriented model previously developed by the authors' group for LRS FRP-confined NAC, can present satisfactory predication performance on LRS FRP-confined RAC. These findings not only provide design guidance for LRS FRP-confined RAC members, but also point to the possibility of the development of a sustainable structural system.